Ruthenium(II) complexes of the tetradentate polypyridyl thioether 1, 2-bis[3′-(2″-pyridyl)-1′-thiapropyl]benzene. (15th March 2020) - Reeves, GorDan T.; Addison, Anthony W.; Zeller, Matthias
Graphical abstract: Several new Ru(II) polypyridyl complexes of the novel tetradentate thioether 1, 2-bis[3′-(2″-pyridyl)-1′-thiapropyl]benzene (Ppes) form from the dinuclear ruthenium(II) complex [Ru(Ppes)2 (µ-Cl)2 ] 2+ via reaction with various bidentate diimines. Facile symmetrical bridge cleavage occurs, producing mononuclear complexes of the form [Ru(Ppes)(L)] 2+, where L is the bidentate diimine. Abstract: Several new Ru(II) polypyridyl complexes of the novel tetradentate thioether 1, 2-bis[3′-(2″-pyridyl)-1′-thiapropyl]benzene (Ppes) form from the dinuclear ruthenium(II) complex [Ru(Ppes)2 (µ-Cl)2 ] 2+ via reaction with various bidentate diimines. Facile symmetrical bridge cleavage occurs, producing mononuclear complexes of the form [Ru(Ppes)(L)] 2+, where L is the bidentate diimine. Redox chemistry shows single-electron Ru(II) → Ru(III) oxidations over a wide range of potentials.